MODERN APPROACHES ON THE RELATIONSHIP BETWEEN EDUCATION AND ECONOMIC GROWTH - Abdukhaparova Dilrabo Mirzakhmat kizi (Scholars Digest Publishing, 2023)
In the modern world, the economic justification of any choice is quite common. This is mainly due to the fact that participants in economic processes expect to make a profit from their investments. But it is not always possible to calculate the effectiveness, which is often associated with a long wait for results, their destruction against the background of other investments, the lack of a direct relationship, etc. All this concerns the education system. Thus, the purpose of this study is to identify the relationship between education and economic growth and to assess this interaction. To do this, the theoretical developments of domestic and foreign researchers on this issue were analyzed, as well as methods for assessing the impact of education on economic growth.The disadvantages due to which the considered approaches lose relevance in the conditions of digitalization of the economy are also studied, forms of changing the evaluation method are developed. An attempt was made to combine quantitative and qualitative assessment to obtain an objective evaluation result.
Keywords: higher education, economics, innovations, distance education, gross domestic product, gross regional product, economic growth, education index, endogenous factor, exogenous factor